(untitled) (Global Journal of Science Frontier Research, 2017)
Adaptability of crops can vary from location to location depending on the agro-ecology of a particular area. Therefore, it is essential to conduct location specific adaptation trial to identify suitable variety/varieites. Accordingly, an adaptation trial of Irish potato varieties was conducted in Bule hora district to identify potato varieties that is better in adaptation, yield and other agronomic characteristics, and pest and disease tolerant. The released varieties (Gudane, Jalane, Marachere, Guassa, Gorobela and Gera) were brought from Holeta Agricultural research center. Local variety was also included. The seven treatments (varieties) were laid out in RCBD with three replications. Significant variation was observed among the varieties for days to flowering, days to maturity, Unmarketable yield, marketable yield, number of tubers per hill, tuber weight per hill, stand count and tuber yield. There was no significant difference for tuber drymatter.